Seeing How It Sounds: Observation, Imitation, and Improved Learning in Piano Playing. Issue 2 (3rd April 2017) - Simones, Lilian; Rodger, Matthew; Schroeder, Franziska
ABSTRACT: This study centers upon a piano learning and teaching environment in which beginners and intermediate piano students ( N = 48) learning to perform a specific type of staccato were submitted to three different (group-exclusive) teaching conditions: audio-only demonstration of the musical task; observation of the teacher's action demonstration followed by student imitation ( blocked observation ); and observation of the teacher's action demonstration while alternating imitation of the task with the teacher's performance ( interleaved observation ). Students submitted to interleaved observation were more proficient at the learned task with no significant differences for students of different proficiency levels.